If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 10v + -7v + -7 = 0 Reorder the terms: 7 + -7 + 10v + -7v = 0 Combine like terms: 7 + -7 = 0 0 + 10v + -7v = 0 10v + -7v = 0 Combine like terms: 10v + -7v = 3v 3v = 0 Solving 3v = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Divide each side by '3'. v = 0 Simplifying v = 0
| -1/x-2=0 | | 5x+5x+4+9=6x+4+3x | | 242=169+13c | | -131=3(3-6n)-2n | | ((7y+9)/6)+((y-6)/3)=4 | | 5x^(2/3)-44x^(1/3)-9 | | h-0.78=2.65 | | (4u-3)/5=4-((7u-2)/4) | | 4x+2x-x+3x= | | (7-3)2+3(8)= | | (4f+13g)(2w)= | | 7/2x-5=4/x+1 | | (4v-4)/3=((v+1)/6)+2 | | =x^2+22x+72 | | 11+21(11)=(13+c)13 | | 12y-10=-11+9y | | 3(x-6)/4=4x+6 | | 3(2n+1)+4(n-2)= | | h/2+7=10 | | 1=n/4-1 | | 20=5x+7x^2 | | 14=9-p | | 2+x/5=0 | | 4+b/-2=-2 | | 0=14d+8d^2 | | (6+y)(2y+5)=0 | | 12x+15=5x+62 | | 5x+x-4=-4 | | 2/3x-1/2y=12 | | (6x-4)-(2x+5)= | | 2/10=b/5 | | Y-12X+4Y+16=0 |